2016
DOI: 10.1002/jcb.25527
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Stem Cells Protect Non‐Stem Cells From Anoikis: Bystander Effects

Abstract: Cancer stem cells (CSCs) are capable of initiation and metastasis of tumors. Therefore, understanding the biology of CSCs and the interaction between CSCs and their counterpart non-stem cells is crucial for developing a novel cancer therapy. We used CSC-like and non-stem breast cancer MDA-MB-231 and MDA-MB-453 cells to investigate mammosphere formation. We investigated the role of the epithelial cadherin (E-cadherin)-extracellular signal-regulated kinase (Erk) axis in anoikis. Data from E-cadherin small hairpi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 61 publications
1
26
0
Order By: Relevance
“…The above results suggested that the derived spheroids are composed of mixed cell populations, including non-CSCs, as previously reported [25]. To test this hypothesis, the percentages of dead and apoptotic cells in both TS#2 and SS#2 spheroids were measured using a live/dead cell viability assay kit and an annexin V-FITC apoptosis detection kit, respectively, according to the manufacturers instructions.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…The above results suggested that the derived spheroids are composed of mixed cell populations, including non-CSCs, as previously reported [25]. To test this hypothesis, the percentages of dead and apoptotic cells in both TS#2 and SS#2 spheroids were measured using a live/dead cell viability assay kit and an annexin V-FITC apoptosis detection kit, respectively, according to the manufacturers instructions.…”
Section: Resultssupporting
confidence: 60%
“…Additionally, these methods may result in the formation of spheroids containing many cells that are not CSCs. A recent report showed that CSC-like cells protect non-CSCs from anoikis and also promote tumor growth [25]. As spheroid bodies themselves display marked cellular heterogeneity, experiments using spheroids should be interpreted as studies of mixed cell populations, not as purified CSCs [29].…”
Section: Resultsmentioning
confidence: 99%
“…A previous report showed that TDO2 facilitates anoikis resistance in triple-negative breast cancer [18], and another study indicated that resistance to anoikis was related to CSC-like cells [30]. Thus, we hypothesized that TDO2 expression may be related to CSC marker expression in ESCC.…”
Section: Relationship Between Tdo2 Expression and The Csc Marker Cd44mentioning
confidence: 84%
“…27 CSCs in several cancers including breast have been shown to be resistant to anoikis, form spheres in nonadherent culture and have enhanced tumor growth capacity. 28 UM cells surviving anoikis showed an increased expression of several markers previously associated with neural crest development and stem cells: CD271, Nestin, and CD166. CD271 has been shown to mark the CSC population in skin melanoma.…”
Section: Discussionmentioning
confidence: 84%